Novel Low-Flying Propeller-Driven Aircraft Concept For Reduced Direct Operating Costs And Emissions - Andreas Johanning and Dieter Scholz (Optimage Ltd., 2012)
This paper presents a novel concept for a fast, lower flying, highly efficient and ecological propeller driven aircraft. The aircraft has a high wing, T-tail and 4 turboprop engines with large propeller diameters decreasing the disc loading and therefore increasing the propeller efficiency. The propeller blades have high sweep angles allowing high cruise Mach numbers at high efficiencies. It is shown that Direct Operating Costs (DOC) can potentially be reduced by about 11 % while reducing trip fuel mass and therefore CO2 emissions by about 14.9 % compared to the reference aircraft Airbus A320.
Keywords: Turboprop; Aircraft design